Analysis Of The Uninhabitable House Social Rehabilitation Program At The Department Of Public Housing Settlement Areas And Land Affairs Surabaya - Norma, Etikasari; Mustofa, Amirul (Socious Journal, 2024)
The objective of this research is to analyze the implementation of the Uninhabitable House Program at the Department of Public Housing, Settlement Areas, and Land Affairs of Surabaya regarding the issue of uneven distribution of program beneficiaries. This study was conducted using qualitative methods and a descriptive approach. Data were obtained through interviews with information sources and documentation in the form of graphs and tables managed by the researchers. The research location is at the Department of Public Housing, Settlement Areas, and Land Affairs of Surabaya. The benefits provided by this research include giving the public insight into the implementation of the program by the responsible department and identifying the main problems and obstacles related to the Uninhabitable House Program in Surabaya. The results of the research indicate that the uneven distribution is due to community leaders who conduct the screening or selection of program beneficiaries not adequately assessing the eligibility for house repairs. Additionally, the program implementation team from the Department of Public Housing, Settlement Areas, and Land Affairs faces challenges in the field. These challenges include issues with beneficiaries who have land disputes or whose land ownership is still under family status. Such problems stem from the beneficiaries themselves, related to land status or personal issues with family members. The researchers recommend closer cooperation between stakeholders, increased socialization from both the DPHSALA and community leaders, and the resolution of individual issues for Beneficiaries.